Stress Attractors in Lattakian Syrian Arabic - shaheen, buthaina (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Stress in Lattakian Syrian Arabic is not sufficiently investigated. The present paper considers a number of issues related to stress in Lattakian Syrian Arabic. Focus is made on attractors of stress. Using the Metrical Stress Theory, data are analysed. Lattakian is shown to variably assign stress to the penultimate. This is due to a difference between non-final CVC syllables and CVG/CVV syllables. Weight in various guises seems to be one main attractor of stress.